STUDENTS' PERCEPTION TOWRADS THE USE OF CODE SWITCHING AS A MEANS OF COMMUNICATION IN EFL CLASSROOM - Desliyanah, Sherly (Jurnal Ilmiah Bina Bahasa, 2021)
This study is aimed to find out the perception of students towards the use of English – Indonesia code switching as a means of communication in learning and teaching process in the classroom. The study was conducted in Stisipol Candradimuka Palembang, with 20 students from all study programs as the sample of study. The result of study showed that 70% of students preferred to use both English and Indonesia as a means of communication while teaching and learning process. Meanwhile, 20% of students preferred to use Indonesia only as mean of communication in the process of teaching and learning in the classroom. And 10% of students preferred to use English only as the means of communication in the classroom. Based on the result of study, it could be concluded that the students preferred to use the code switching of English and Indonesia as a means of communication in the process of English teaching and learning in the classroom.